The Leadership Role of the Principal in Improving Teacher Performance Discipline in Mas Nur Ibrahimy Rantauprapat - Hurin Nurjannah Hsb; Junita Junita (Budapest International Research and Critics University, 2022)
Every human being must have and need a supreme leader (top leadership) or the highest manager who must carry out leadership or management activities for the whole and unity. In reality, many people are not enough to be controlled by a leader, that's why the terms leader and leader are used. The purpose of this study was to determine the role of the principal's leadership in improving the discipline of teacher performance at MAS Nur Ibrahimy Rantauprapat. This type of research used is descriptive qualitative, the source of the data is obtained from the principal of MAS Nur Ibrahimy and teachers, as well as other documents. This data collection was carried out using the interview method, and documents, so that the instruments were researchers, interview sheets, and documentation.Have a supervisory system that must be implemented in schools to improve teacher performance discipline, Implement discipline enforcement for teachers, Provide an example of principal leadership by being disciplined.